Persiapan Peralatan dan Dokumen Sebelum Melaksanakan Aktivitas Bongkar Curah Kering pada PT Wahana Intradermaga Niaga Belawan - Fikri Rakawitan; Fadiyah Hani Sabila (JURNAL RISET MANAJEMEN (JURMA), 2023)
The purpose of this research is to find out about the preparation of equipment and documents before carrying out dry bulk unloading activities at PT Wahana Intradermaga Niaga Belawan. Preparation of equipment and documents before unloading dry bulk is a crucial step in ensuring smooth, safe and effective operations at ports and distribution facilities. This process involves moving goods in dry form, such as grain, coal, and wheat, from a means of transportation to a storage area or final destination. In the process of preparing equipment and documents before carrying out dry bulk unloading activities, problems often occur such as damage to unloading equipment and delays in documents caused by lack of information and difficulties in compiling complete documents, so that the service will have a less effective impact and hinder the implementation of loading and unloading. In addition, the author will highlight the importance of complete documents, such as loading and unloading permits, contractual agreements, and security documentation, to ensure legal compliance and smooth operations. This research method uses the field research method (field research) and the library research method (retrieval of data from the library). The results of this research are that by paying careful attention to the preparation of equipment and documents before starting dry bulk unloading activities, companies can increase operational efficiency, reduce the risk of accidents, ensure legal compliance, and maintain safety for all parties involved.